The Cambridge Companion to the Essay / Ed. - Kindley, Evan; Wittman, Kara (Cambridge : Cambridge University Press, 2023)
"This Companion, written by a diverse group of scholars for an audience of students and professors, considers the history, theory, and aesthetics of the essay form from the sixteenth century to the present"--
Remembering the essay / Jeff Dolven -- The personal essay / Merve Emre -- The critical essay / Frances Ferguson -- The nature essay / Daegan Miller -- The essay in theory / Kara Wittman -- Essay and experiment / Julianne Werlin -- Essay, enlightenment, revolution / Anahid Nersessian -- The essay, abolition, and racial blackness / Jesse McCarthy -- The utopian essay / Ignacio M. Sánchez-Prado -- Ethics and the essay / David Russell -- Essay and empire / Saikat Majumdar -- Unqueering the essay / Grace Lavery -- The essay and the novel / Jason Childs -- Lyric, essay / Claire Grossman, Juliana Spahr, and Stephanie Young -- The photograph as essay / Kevin Adonis Browne -- The essay film / Nora M. Alter -- The essay online / Jane Hu.
Keywords: Essay -- History and Criticism; LITERARY CRITICISM / Semiotics & Theory